2006
DOI: 10.1063/1.2200398
|View full text |Cite
|
Sign up to set email alerts
|

On the band gap of CuAlO2 delafossite

Abstract: In this letter, we discuss the electronic structure of copper aluminate ͑CuAlO 2 ͒ on the basis of absorption measurements at low temperature and under high pressure in single crystals and thin films, combined with ab initio electronic structure calculations. The indirect character of the fundamental transition could be clearly established through the photon energy dependence of the absorption edge as measured in single crystals, yielding a band gap ͑plus a phonon͒ of 2.99± 0.01 eV at room temperature. An indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 21 publications
11
63
1
Order By: Relevance
“…Band structure calculations predict a negative pressure coefficient for the CuScO 2 direct transition of -4.9 meV/GPa, which agrees fairly well with the experimental value. A similar value for the theoretical pressure coefficient of the direct gap is also obtained for the direct transition in CuAlO 2 (-6 and -4 meV/GPa at the L-and P-points respectively [7]), in contrast to the small, but positive experimental value of its absorption tail. This discrepancy can be explained by taking into account the resonant nature of the direct exciton in this compound.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Band structure calculations predict a negative pressure coefficient for the CuScO 2 direct transition of -4.9 meV/GPa, which agrees fairly well with the experimental value. A similar value for the theoretical pressure coefficient of the direct gap is also obtained for the direct transition in CuAlO 2 (-6 and -4 meV/GPa at the L-and P-points respectively [7]), in contrast to the small, but positive experimental value of its absorption tail. This discrepancy can be explained by taking into account the resonant nature of the direct exciton in this compound.…”
Section: Discussionsupporting
confidence: 56%
“…X-ray diffraction shows that the volume of the 3R unit cell of CuAlO 2 is 22% smaller than that of CuScO 2 [5,6], which is consistent with the size of the trivalent cation. It has been shown that CuAlO 2 has an indirect gap (plus a phonon) of 2.99 ± 0.01 eV at room temperature and pressure, with the lowest energy direct transition occurring at 3.53 ± 0.01 eV [7]. These experimental results are supported by several band structure calculations [7,8].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…A considerable amount of work was developed in the last years in the study of CuAlO 2 , mostly focused in the growth and the optical and electrical characterization (see reference [4]), but many basic properties of CuAlO 2 remain unknown, for example very recently has been proved experimentally that the fundamental gap is indirect [3].…”
Section: Introductionmentioning
confidence: 99%
“…Also Pellicer Porres et al [393] questioned the interpretation of the low energy peaks as indirect transitions, as the absorption coefficient is more than two orders of magnitude larger than in typical indirect absorption edges. The most promising defects that could be responsible are oxygen interstitials O i , as DFT calculations within the LDA predict low formation energies and the introduction of states in the gap at 0.7 and 1.4 eV [409].…”
Section: Accurate Calculations Of Band Structuresmentioning
confidence: 99%